C^{*}-Algebras. - Doran, Robert S. (Contemporary Mathematics Ser., 1994)
This volume contains the proceedings of an AMS Special Session held at the Joint Mathematics Meetings in San Antonio in January 1993 to celebrate the first fifty years of C^*-algebra theory. The book contains carefully written expository and research articles by leaders in the field. Also included is a reprinting of the original 1943 paper on C^*-algebras by Gelfand and Neumark, which has had such a profound influence on the field. The volume covers a broad spectrum of topics, including the Gelfand-Neumark theorems, C^*-algebras and quantization, projections in C^*-algebras, Mackey's theory of.